DESKRIPSI KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS VII PADA MATERI OPERASI HITUNG CAMPURAN BILANGAN BULAT - Suryadi Suryadi; Hamdani Hamdani; Ahmad Yani T (Universitas Tanjungpura, 2022)
Problem solving is one of the goals in learning mathematics. In solving problems students must use steps to solve them, including in solving story problems. The ability needed to solve a story problem is not only specific skills or algorithms, but also the ability to prepare a plan or strategy that will be used in solving problems. The purpose of this study is to describe the use of Polya problem solving steps by students in solving story problems on mixed integer operation material. This research is a descriptive qualitative research. The subjects of this study were four students chosen randomly or randomly. While this research instrument is a written test about a story that has been validated by a mathematics teacher and unstructured interviews. Based on the analysis obtained shows that not all students use Polya's problem solving steps in solving story problems, this is indicated by the way students work on the results of written tests and interviews.